Dual α-globin-truncated erythropoietin receptor knockin restores hemoglobin production in α-thalassemia-derived erythroid cells - Simon N. Chu; Eric Soupene; Devesh Sharma; Roshani Sinha; Travis McCreary; Britney Hernandez; Huifeng Shen; Beeke Wienert; Chance Bowman; Han Yin; Benjamin J. Lesch; Kun Jia; et al. (Cell Reports)
Summary: The most severe form of α-thalassemia results from loss of all four copies of α-globin. Postnatally, patients face challenges similar to β-thalassemia, including severe anemia and erythrotoxicity due to the imbalance of β-globin and α-globin chains. Despite progress in genome editing treatments for β-thalassemia, there is no analogous curative option for α-thalassemia. To address this, we designed a Cas9/AAV6-mediated genome editing strategy that integrates a functional α-globin gene into the β-globin locus in α-thalassemia patient-derived hematopoietic stem and progenitor cells (HSPCs). Incorporation of a truncated erythropoietin receptor transgene into the α-globin integration cassette significantly increased erythropoietic output from edited HSPCs and led to the most robust production of α-globin, and consequently hemoglobin tetramers. By directing edited HSPCs toward increased production of clinically relevant erythroid cells, this approach has the potential to mitigate the limitations of current treatments for the hemoglobinopathies, including low genome editing and low engraftment rates.